Community Service Sentencing and Its Challenges in Implementation: A Case Study for Zambia (Global Journal of Human-Social Science, 2024)
This article presents the challenges of the implementation of community service sentencing in Zambia This study defines what community service sentencing is and further highlights the advantages and disadvantages of community service sentencing It discusses community service sentencing in Zambia based on variables such as the historical context implementation and challenges The study further delves into other areas such as the legal framework of community service sentencing in Zambia an exploration of the roles of Non-Governmental Organizations on these sentencings effectiveness and impact of community service sentencing It will go further and provide a comparative analysis of community service sentences in other countries to Zambia and conclude by identifying gaps and issues that exist after the thorough research
Keywords: community service sentencing; nongovernmental organizations (NGOs); recidivism; custodial sentencing; rehabilitation; reintegration; punishment